The effect of metyrosine on oxidative gastric damage induced by ischemia/reperfusion in rats. Biochemical and histopathological evaluation - Çimen,Orhan (2018)
Abstract Purpose: To investigate the effect of metyrosine against I/R induced gastric damage in rats. Methods: Eighteen albino Wistar male rats were divided into groups; gastric I/R (GIR), 50 mg/kg metyrosine+gastric I/R (MGIR), and sham (SG) groups. 50 mg/kg metyrosine was given to the MGIR group, and distilled water was given to the GIR and SG groups by the oral gavage. After 30 minutes, 25 mg/kg thiopental sodium was injected intraperitoneally. Ischemia was achieved for 1 hour by clamping the celiac artery of the MGIR and GIR groups, then reperfusion was achieved for 3 hours. After that, animals were killed with 50 mg/kg thiopental. Biochemical and histopathological examinations performed on the gastric tissues. Results: Metyrosine decreased the MDA and MPO and the increased the tGSH and SOD. In addition, it reduced inflammation by suppressing the decrease of COX-1 and the increase of COX-2. Histopathologically, metyrosine decreased symptoms caused by I/R such as mucosal necrosis, hemorrhage, edema, PMNL infiltration, and dilated congested blood vessels. Conclusions: Metyrosine prevented the I/R induced oxidative stress in the gastric tissue. Metyrosine may be beneficial for gastric I/R injury.